2012
DOI: 10.1186/1477-7819-10-106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of extra capsular lymph node involvement in patients with extra-hepatic bile duct cancer

Abstract: BackgroundLymph node metastasis is one of the most important prognostic factors for extra-hepatic bile duct carcinoma (ExHBDC). Extra capsular lymph node involvement (ExCLNI) is the extension of cancer cells through the nodal capsule into the perinodal fatty tissue. The prognostic impact of ExCLNI has been shown to be significant mainly in head and neck malignancies. Recently, the prognostic impacts of ExCLNI have evaluated in gastrointestinal malignancies. However no data is available regarding the incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…In the same regard, the current study systematically performed lymph node dissection and found that one‐half of patients had positive lymph node status, but the results did not confirm any impact of lymph node involvement on OS ( P = 0.38) or DFS (0.88). Similarly, Noji et al demonstrated that extracapsular lymph node involvement had no impact on the survival ( P = 0.418) of DCC after resection with curative intent . The results of the present study support several other independent risk factors associated with poor DFS: (i) male gender (HR = 3.29 [1.6–6.78], P = 0.001); (ii) need for organ resection (HR = 7.1 [2.17–23.23], P = 0.001); (iii) vascular invasion (HR = 2.71 [1.41–5.2]) P = 0.003); and (iv) abdominal infection following surgery (HR = 3.39 [1.46–7.88] P = 0.004).…”
Section: Discussionsupporting
confidence: 85%
“…In the same regard, the current study systematically performed lymph node dissection and found that one‐half of patients had positive lymph node status, but the results did not confirm any impact of lymph node involvement on OS ( P = 0.38) or DFS (0.88). Similarly, Noji et al demonstrated that extracapsular lymph node involvement had no impact on the survival ( P = 0.418) of DCC after resection with curative intent . The results of the present study support several other independent risk factors associated with poor DFS: (i) male gender (HR = 3.29 [1.6–6.78], P = 0.001); (ii) need for organ resection (HR = 7.1 [2.17–23.23], P = 0.001); (iii) vascular invasion (HR = 2.71 [1.41–5.2]) P = 0.003); and (iv) abdominal infection following surgery (HR = 3.39 [1.46–7.88] P = 0.004).…”
Section: Discussionsupporting
confidence: 85%
“…Previous reports have shown that lymph node metastases are the strongest prognostic factors for survival in perihilar cholangiocarcinoma 8,[14][15][16] . Predicting the N category in the preoperative period is a very important topic in perihilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our data showed that PLR correlated with tumor extent and histopathologic grade in hilar cholangiocarcinoma, suggesting that PLR can reflect the degree of malignancy in this disease. In pancreatic cancer, one previous study reported that preoperative PLR represented a significant independent prognostic index and had prognostic value independent of tumor size and lymph node ratio 8,[14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall 3986 patients with a median age of 66 (range 58-70) were described and 2128 patients (53%) suffered from perihilar cholangiocarcinoma ( Table 1). [12][13][14][15][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In addition, 11 studies reporting exclusively perihilar The median number of lymph node count was reported in all 20 studies ranging from 2-24 lymph nodes (Fig 2). In 60% of the studies (n=12) exclusively regional lymphadenectomy was described.…”
Section: Descriptive Cohortmentioning
confidence: 91%